2022
DOI: 10.1177/1420326x221087571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the air supply angle of swirling diffusers on the air diffusion performance index in a vehicle assembly workshop

Abstract: Airflow improvement in a large industrial building is one of the most effective ways to improve the thermal comfort of workers. Air Diffusion Performance Indices (ADPI) of an industrial workshop area under different air supply angles (15°, 30°, 45°, 60°, 75° and 90° in summer and 90° in winter) of the ceiling-mounted swirling diffusers were evaluated by on-site measurements and computational fluid dynamics (CFD) modelling. The measurement data was used to verify the CFD numerical model. The temperature and vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Introduction of P-ADPI. The air distribution characteristic index ADPI 27 is the percentage of people who feel comfortable indoors; it is used to measure the thermal comfort of people in a uniform local heating environment. It is the ratio of the number of measuring points with temperature and wind speed meeting the effective temperature difference (4ET) between À1.7 ∼ + 1.1°C and the total number of measuring points, which can be calculated using equation ( 3) Equation ( 4) determines the effective temperature difference (4ET) with indoor temperature and velocity…”
Section: Characteristic Parameter Definitionmentioning
confidence: 99%
“…Introduction of P-ADPI. The air distribution characteristic index ADPI 27 is the percentage of people who feel comfortable indoors; it is used to measure the thermal comfort of people in a uniform local heating environment. It is the ratio of the number of measuring points with temperature and wind speed meeting the effective temperature difference (4ET) between À1.7 ∼ + 1.1°C and the total number of measuring points, which can be calculated using equation ( 3) Equation ( 4) determines the effective temperature difference (4ET) with indoor temperature and velocity…”
Section: Characteristic Parameter Definitionmentioning
confidence: 99%
“…The operating conditions of HVAC systems affect not only droplet transmission, but also many factors, including operating costs, ventilation effects and thermal comfort conditions. [15][16][17] Since the tilt angle of the HVAC system, one of the various operating conditions, was an important factor in determining the indoor flow pattern, various studies have been conducted. 18,19 Xin et al 20 studied the operation performance and energy consumption of the standing type of air conditioners according to different installation positions, and they showed that the optimum cooling performance and removal of volatile organic compounds (VOC) occurred when the standing type of the air conditioner was installed diagonally opposite the door.…”
Section: Introductionmentioning
confidence: 99%